The evaluation of oxidative damage of DNA after poisoning with nerve agents - Kassa, Jiří; Štětina, Rudolf (Journal of Applied Biomedicine, 2019)
The potency of three nerve agents (sarin, soman, tabun) to induce oxidative damage of DNA in lymphocytes, liver and brain during lethal or sublethal poisoning was investigated. The single strand breaks or oxidative base DNA damage was evaluated with the help of Comet assay and a specific enzyme able to detect oxidative bases of DNA (endonuclease III). While sarin and soman administered at sublethal doses corresponding to 50% of their LD50 values were not able to induce oxidative damage of DNA, their lethal dose (LD50) induced the significant increase of the number of oxidative bases in DNA of hepatocytes. In addition, tabun administered at lethal dose (LD50) induced significant increase of the number of single strand breaks and oxidative bases of DNA in glial cells isolated from pontomedullar brain region. Thus, some nerve agents were able to induce oxidative damage in the peripheral as well as central compartment but only in the case of severe poisoning caused by lethal doses of nerve agents. This non-cholinergic effect of nerve agents has probably consequences with nerve agents-induced hypoxic status during acute cholinergic crisis and it can contribute to their long-term toxic effects.
Keywords: sarin; organofosfáty; Organophosphates; Sarin; Oxidative Stress; oxidační stres; Humans; soman; Soman; DNA; lidé